Assessment of Challenges Encountering Nurses in Delivering Care to Patients with Cerebrovascular Accident - Lilu, Firas Khider Abdullah; Al-Jubouri, Mohammed Baqer Abbas (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): The aim of the study is to assess the challenges encountered by nurses in delivering care for patients with cerebrovascular accidents in the neurological departments. Methods: A descriptive study conducted purposely on 80 nurses working in the neurological departments in Baquba Teaching Hospital from January 9th to February 20th, 2023. Data analysis encompassed the application of both descriptive and inferential statistics. Result: Nuero-specialized nurses faced many challenges namely: workload and role conflict, psychological load, inadequate resources, and feeling of increased responsibilities. The study also found a significant relationship between challenging workloads and nurse’s workplaces, and their level of education. Conclusions: Nurses encounter challenges psychological load, inadequate resources, and increased responsibilities that hinder the delivery of nursing care for cerebrovascular accidents patients. Recommendations: This study recommends that healthcare organizations prioritize workload management strategies, supply the important resources, provide psychological support for nurses, offer education and training programs, and conduct further research about nursing challenges in different healthcare settings.